O trabalho doméstico de adolescentes: naturalização da exclusão e submissão - Félix, José Fontes (2010)
This work demonstrates important aspects of domestic work performed by adolescents between 16 and 18 years in residential spaces. This is to highlight the process of naturalization of invisibility, their source of insecurity and social exclusion, in view of the strong personal relationship of domination. Pointing out the relations of pseudo-affection that can obscure the exploitation of domestic labor. Highlight a preliminary discussion on the composition of social relations embedded in the context of domestic work, with emphasis on reflection on the condition of subordination of young domestic workers as a result of a process of socialization consists of relations of domination - gender and social class, resulting in formation of social identity-forming negative stigma. This paper results from a survey of the work of young maids, held in the city of Aracaju, whose main objective was to understand how they operated the differences and inequalities in the relations of domestic based, including information on adolescents' own. Fieldwork was conducted from August 2009 to January 2010 and data collection techniques were used oral history / life history, questionnaires and use of semi-structured interviews, as well as secondary data from PNAD / IBGE which formed the basis of comparative national situation and local context. It emphasizes the links of domestic work involving teenagers question the lifestyles of working class who are confronted by the various "systems" for each home, which leads to the development of adaptation strategies that make possible the coexistence of a stranger the house at the other. It focuses on how the work goes into their lives in terms of socialization offered by working families to their children's, and as this class habitus is adequate for the job market in domestic employment through a socialization process that sometimes opposes and now reinforces the practices and values seized in family socialization